Malaria risk mapping in Sri Lanka - Results from the Uda Walawe area: Proceedings of a workshop held in Embilipitiya, Sri Lanka, 29th March 2001 - Klinkenberg, Eveline (International Water Management Institute, 2001)
Proceedings of a workshop held in Embilipitiya, Sri Lanka, 29th March 2001. Presents preliminary findings on malaria patterns and possible risk factors and describes the progress of IWMI research towards developing a risk map for Sri Lanka. It also contains presentations by Regional Malaria Officers, and other officials involved in malaria control, on areas of high malaria risk within their districts.